Diversity, structures assemblages and production of benthic communities on artificial reefs, a comparative case study in the English Channel. Issue 1 (1st July 2022) - Vivier, B; Dauvin, J C; Navon, M; Chasselin, L; Deloor, M; Rusig, A M; Mussio, I; Boutouil, M; Salaün, J; Claquin, P
Abstract: In this study, the diversity and structures assemblages of benthic communities present on artificial reefs (AR) immersed for 5 years were monitoring during a full year in 2020. The comparison of two different sites Bernières in the Bay of Seine and Cherbourg in the central part of the English Channel brings innovative results on the efficiency of such structures. Benthic fauna and macroalgae communities were studied; several biotic indices like Shannon-Wiener diversity index were calculated. Benthic fauna was classified according to their trophic group and the biomass was estimated. Our results pointed out strong differences for several indicators between sites and seasons. Benthic fauna was more abundant in the Bay of Seine and more diversified than in the Bay of Cherbourg. Primary producers' diversity and biomass were higher in the Bay of Cherbourg and dominated by Rhodophyceae species. Primary production results showed that the Bay of Cherbourg was a more productive system than the Bay of Seine. This study highlighted the efficiency of such structures to create habitats and promote biomass and diversity of associated living communities. In comparable conditions, different systems were highlighted: a "primary producer reef" and a "primary consumer reef".